Enhanced the anxiety monitoring system among athletes with IoT for sports performance : A review - Wan Nurlisa, Wan Ahmad; Mohd Azrul Hisham, Mohd Adib; Sut Txi, Mon Redee (Editura Universitatii din Pitesti, 2022)
Modern sports have made considerable utilization of advancements in robust modern technology for anxiety monitoring systems (AMSs). This study introduces the AMS for sports athletes based on the Internet of Things (IoT) which accurately identifies athlete performance. In sports applications, the technological devices integrated with IoT systems have been extensively used for the real-time utilization of the athlete's health conditions for anxiety factors, instead of tracking real-time location between the athlete and the coach. Several anxiety parameters were discussed in this study, due to athletes' inconsistency in performance issues. This review model incorporates athlete psychological and physiological anxiety parameters and multiple sensors of an AMS-IoT to enhance overall sports performance. An IoT health monitoring system was explicitly designed based on a sports application, and encompasses four primary aspects: Sensing, networking, data processing and an application layer. The IoT technology can connect functions between sensors, microcontrollers, cloud systems, technological devices, and digital equipment for the targeted users. The communication between IoT devices mainly involves wireless communication, and accessibility is open with any Internet-enabled device. Based on the review, using an AMS during games results in improved readiness for athletes during the actual competitions. The coaches can provide appropriate training to the athletes according to their current health conditions. Therefore, the can AMS greatly assists the coaches in designing training activities for their athletes. It is highlighted that an efficient monitoring system can produce consistent and excellent sports performance according to the athlete's individual fitness level. The further study emphasizes that AMS powered by IoT technology merits further investigation based on athletes and their sport’s needs.